The Impact of Financial Development on Carbon Emissions and Energy Consumption Patterns in OPEC Member Countries: An Econometric Analysis - Heidari, Hossein; Sotoudeh Nia Korani, Salman (Business, Marketing, and Finance Open, 2025)
Energy plays a crucial role in the economic development of countries. Achieving economic development in developing nations appears unlikely without adequate energy resources. Over recent decades, energy demand has been rising due to population growth and changes in the economic structure of nations. This growing demand for fossil fuels has led to increased greenhouse gas emissions. In a pioneering approach, this study investigates the relationship between financial development, carbon emissions, and energy consumption in OPEC member countries over the period from 2013 to 2024. By employing econometric techniques such as the Generalized Method of Moments (GMM), Dynamic Ordinary Least Squares (DOLS), and Fully Modified Ordinary Least Squares (FMOLS), the results indicate that financial development in these countries has had a significant and positive impact on increased environmental pollution and energy consumption. These findings suggest that financial development in the examined countries has not led to the advancement of environmentally friendly technologies and may have even exacerbated environmental impacts by intensifying industrial activities.